A glutamine-based single α-helix scaffold to target globular proteins - Albert Escobedo; Jonathan Piccirillo; Juan Aranda; Tammo Diercks; Borja Mateos; Carla Garcia-Cabau; Macarena Sánchez-Navarro; Busra Topal; Mateusz Biesaga; Lasse Staby; Birthe B. Kragelund; Jesús García; et al. (Nature Communications, 2022)
Targeting biomedically relevant protein-protein interactions is a long-lasting challenge in medicinal chemistry. Here, the authors develop a single α-helical peptide scaffold that can be tailored to target globular proteins of biomedical interest.